2016
DOI: 10.1007/s12576-016-0509-5
|View full text |Cite|
|
Sign up to set email alerts
|

Epac activation inhibits IL-6-induced cardiac myocyte dysfunction

Abstract: Pro-inflammatory cytokines are released in septic shock and impair cardiac function via the Jak-STAT pathway. It is well known that sympathetic and thus catecholamine signaling is activated thereafter to compensate for cardiac dysfunction. The mechanism of such compensation by catecholamine signaling has been traditionally understood to be cyclic AMP-dependent protein kinase (PKA)-mediated enforcement of cardiac contractility. We hypothesized that the exchange protein activated by cAMP (Epac), a newly identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Recently, several reports have identified the roles of Epac in the development of cardiac diseases including arrhythmias. 10,11,[13][14][15][16][17] These findings indicate that inhibition of Epac function may be a novel and useful strategy for the treatment of arrhythmias. However, there have been no reports on the antiarrhythmic effects or cardiac side-effects of Epac inhibitors in vivo.…”
mentioning
confidence: 93%
“…Recently, several reports have identified the roles of Epac in the development of cardiac diseases including arrhythmias. 10,11,[13][14][15][16][17] These findings indicate that inhibition of Epac function may be a novel and useful strategy for the treatment of arrhythmias. However, there have been no reports on the antiarrhythmic effects or cardiac side-effects of Epac inhibitors in vivo.…”
mentioning
confidence: 93%
“…For example, activation of EPAC1 leads to SOCS3 induction, blockade of IL6 JAK/STAT3 signalling and potentiation of barrier function in vitro and in vivo, in normal mice [ 36 ]. Moreover, activation of EPAC in cardiac myocytes attenuates the inhibitory effect of IL6 on cardiac function and contractility in response to isoproterenol, most likely through inhibition of the JAK/STAT3 signalling by SOCS3 [ 37 ]. Using high throughput screening (HTS) we identified a novel ligand (I942) that exhibits agonist properties against EPAC1, but not EPAC2.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has been reported that activation of Epac1 induces SOCS3 gene expression in various types of cells, i.e. cardiocyte (27), vascular endothelial cell (28) and retinal ganglion cell (29). In this study, we observed that Epac activation significantly up-regulated the expression of SOCS3 while inhibited the expression of p-STAT3 and MCP-1 in kidney tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the manipulation of SOCS3 expression would be imperative and is a therapeutic target for DN. Additionally, it has been reported that Epac1 induces SOCS3 gene expression in various types of cells, including cardiocyte (27), vascular endothelial cells (28) and retinal ganglion cells (29). Based on these perspectives, we hypothesized that activation of Epac may protect against the inflammation injury by targeting SOCS3 gene expression in the context of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%